2012
DOI: 10.3892/ijmm.2012.904
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profile of organ culture-stored corneal epithelium: Lgr5 is a potential new phenotypic marker of residual human corneal limbal epithelial stem cells

Abstract: Abstract. Long-term preservation of corneal limbal epithelium may decrease its quality and change the molecular signature of the limbal epithelial stem cells. In this study we have investigated the molecular profile of isolated corneal epithelial cells that have been in storage for an extended time. Isolated cells were characterised by the expression profile of different cytokeratins and markers of squamous metaplasia (vimentin and α-actin). Furthermore, we examined global markers of adult stem cells including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Ex vivo expansion of LECs involves the culture of LECs harvested either from the patient [11], a living relative [16], or a cadaver [17]. It has been suggested that limbal tissue that is taken from a cadaver donor should be placed onto the recipientʼs eye within 72 hours of the donorʼs death in order to maintain cell viability [18,19]. However, it is a common practice in the United Kingdom and Europe to store corneoscleral discs intended for corneal transplantation for up to 4 weeks in an organ culture medium at 28-37 °C [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo expansion of LECs involves the culture of LECs harvested either from the patient [11], a living relative [16], or a cadaver [17]. It has been suggested that limbal tissue that is taken from a cadaver donor should be placed onto the recipientʼs eye within 72 hours of the donorʼs death in order to maintain cell viability [18,19]. However, it is a common practice in the United Kingdom and Europe to store corneoscleral discs intended for corneal transplantation for up to 4 weeks in an organ culture medium at 28-37 °C [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced by the rapidly increasing numbers of manuscripts published over the last two decades with the keyword “limbal stem cell” searchable in PubMed (Figure 1). The quest for a bona fide LSC marker has lead to the discovery of a number of molecules that can potentially be utilized as either positive selection markers such as p63 [15], Lgr5 [16], Tcf4[17], CD157 [18], CD71 low /Integrin α6 high [19], TrkA [20], N-Cadherin [21], ABCG2 [22, 23], Cytokeratin 15[24] and ABCB5[25], or as negative selection markers, e.g. ALDH dim [26], RHAMM bright [26] and Connexin-43 [27].…”
Section: Introductionmentioning
confidence: 99%
“…LGR5 was primarily known as a marker of self-renewing stem cells in rapidly proliferating epithelia under physiological conditions or upon injury, including the stomach [ 3 ], small intestine, colon [ 4 ], and so on [ 5 6 7 8 9 10 ]. In the visual system, it has been reported that LGR5 was detected in only two ocular tissues: the cornea in human [ 11 12 13 ] and the retina in mouse. LGR5 expressing retinal amacrine cells of mouse retina were the first piece of evidence that LGR5 was also expressed in neuronal but not stem cell lineage [ 14 15 ], and were known to possess regenerative capacity and function as an endogenous regenerative source in adult mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%